The incest crime in Colombia: the reasons for its decriminalization (2011)
Incest is a criminal offence in Colombia and in many other american and european jurisdictions, although exceptions are also present. The cultural practice of the avoidance of incest is also universal. This is probably due to the survival advantage for gr